Structural Aspects of Thermally Cleavable Adducts Derived from the Reaction of Imidazolines with Isocyanates - Laue, Andreas; Preuß, Andrea; Heck, Manuel; Martin, Mandy; Binner, Marcus; Rüffer, Tobias; Anders, Susann; Werner, Carsten; Kroll, Lothar; Lang, Heinrich; Spange, Stefan (Synthesis, 2016)
The reaction of isocyanates with substituted imidazolines and the thermally induced cleavage of the resulting adducts are presented. For this purpose, reactions of various isocyanates [ethyl isocyanate, p-methylphenyl isocyanate, phenyl isocyanate, p-(trifluoromethyl)phenyl isocyanate] with 1-alkylimidazoline derivatives have been studied as a function of the substituent at the 2-position of the imidazoline ring. Three equivalents of isocyanate react with one equivalent of 1-ethylimidazoline to give a stoichiometric well-defined adduct. However, 1-ethyl-2-isopropylimidazoline reacts with isocyanates at 0 °C in another way, with formation of 2:1 adducts which belong to the family of 1,3-diphenyltetrahydroimidazo[1,2-a][1,3,5]triazine-2,4(1H,3H)-diones. The reaction of 1-ethyl-2-methylimidazoline with aromatic isocyanates at 0 °C also leads to 2:1 adducts, in this case of a malonamide type, which can react at 60 °C with an additional isocyanate equivalent to give the known pyrimidinediones. Thermal analysis (TG-MS/DSC) and trapping reactions with nucleophilic reagents, such as diphenylamine, show the release of isocyanate during the thermally induced cleavage reaction. Thus, blocked isocyanates are available by the reaction of isocyanates with 1-ethylimidazoline or 1-ethyl-2-isopropylimidazoline.
Keywords: blocked isocyanates; imine bases; isocyanates; imidazolines; amidine/isocyanate adducts